Two‐fold increase in the HIV viral load suppression rate along with decreased incidence over six years in Ndhiwa sub‐county, Kenya. Issue 12 (28th October 2021) - Conan, Nolwenn; Badawi, Mahmoud; Chihana, Menard L.; Wanjala, Stephen; Kingwara, Leonard; Mambula, Christopher; Ngugi, Catherine; Okomo, Gordon; Opollo, Valarie; Salumu, Leon; Nesbitt, Robin; Szumilin, Elisabeth; et al.
Abstract: Background: HIV‐positive individuals who maintain an undetectable viral load cannot transmit the virus to others. In 2012, an HIV population‐based survey was conducted in Ndhiwa sub‐county (Kenya) to provide information on the HIV local epidemic. We carried out a second survey 6 years after the first one, to assess progress in HIV diagnosis and care and differences in the HIV prevalence and incidence between the two surveys. Methods: A cross‐sectional, population‐based survey using cluster sampling and geospatial random selection was implemented in 2018, using the same design as 2012. Consenting participants aged 15–59 years were interviewed and tested for HIV at home. HIV‐positive individuals received viral load testing (viral suppression defined as <1000 copies/ml) and Lag‐Avidity EIA assay (to measure recent infection). The 90–90–90 UNAIDS indicators were also assessed. Results: Overall, 6029 individuals were included in 2018. HIV prevalence was 16.9%. Viral suppression among all HIV‐positive was 88.3% in 2018 (vs. 39.9% in 2012, p < 0.001). HIV incidence was 0.75% in 2018 vs. 1.90% in 2012 ( p = 0.07). In 2018, the 90–90–90 indicators were 93%–97%–95% (vs. 60%–68%–83% in 2012). Conclusion: A two‐fold increase in the HIV viral load suppression rate along with a decreasing trend in incidence was observed over 6 years in Ndhiwa sub‐county. Achieving high rates of viral suppression in HIV populations that can lead to reducing HIV transmission in sub‐Saharan contexts is feasible. Nevertheless, we will need further efforts to sustain this progress.